The protective effect of Eruca sativa against lipid metabolic abnormalities induced by dioxin in male rats. Issue 1 (31st December 2022) - El-Gayar, Hussam A; Salem, Eman T; Edrees, Gamal M
ABSTRACT: 2, 3, 7, 8-Tetrachlorodibenzo-p-dioxin (TCDD) is a toxic environmental compound that causes a deleterious effect on lipid metabolism. This study was conducted to evaluate the protective effect of ethanolic Eruca sativa leaves extract against dioxin-induced lipid metabolic abnormalities in male Rattus rattus. For 5 weeks, Eruca sativa leaves extract (500 mg/kg) was co-administered with dioxin (100 ng/kg) daily via gastric intubation. The concomitant treatment with both dioxin and Eruca sativa extract nearly approached the concentration of serum cholesterol, high-density lipoprotein, γ-glutamyltransferase, in addition to testicular concentration of phospholipids, and the activities of both alkaline phosphatase and acid phosphatase activities. In addition, we have noticed a decline in serum concentration of triglycerides, very low- and low-density lipoprotein, total lipid, phospholipid, alkaline phosphatase, acid phosphatase, and lactate dehydrogenase as well as testicular cholesterol, triglyceride, total lipid, γ- glutamyltransferase, and lactate dehydrogenase activities have shown significant (p < 0.05) decreases. Notably, these alterations were not achieved to the control value relative to the dioxin-treated rate. In conclusion, the protective effects of Eruca sativa leaves extract are attributed to its antioxidant effect and fatty acid content.